2010
DOI: 10.1007/s11136-010-9793-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of reporting health-related quality of life outcomes in randomized clinical trials: implications for clinicians and quality of life researchers

Abstract: Current practice of reporting HRQL outcomes in RCTs remains highly variable, both with regard to quality of reporting and the patterns of data analysis and presentation. This variation presents challenges for clinicians to apply these data in clinical practice. Consistent reporting practices, which are interpretable by clinicians, are required, as are processes to achieve this consistency in future reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 26 publications
(33 reference statements)
9
93
0
Order By: Relevance
“…Prior reviews indicated suboptimal PRO reporting [10,11], which limited the potential for PRO evidence to impact practice, thus representing a waste of research effort. CONSORT-PRO aims to facilitate translation of high-quality PRO evidence to clinical practice and policy [12].…”
Section: Preliminary Evidence On the Uptake Use And Benefits Of The mentioning
confidence: 99%
“…Prior reviews indicated suboptimal PRO reporting [10,11], which limited the potential for PRO evidence to impact practice, thus representing a waste of research effort. CONSORT-PRO aims to facilitate translation of high-quality PRO evidence to clinical practice and policy [12].…”
Section: Preliminary Evidence On the Uptake Use And Benefits Of The mentioning
confidence: 99%
“…In a review published in 2011, Brundage et al reported that in an identified sample of 794 RCTs, PROs were primary endpoints in just 26% of the total trials; in the 56% of the total trials where the rationale for the selected PROs was documented, 28% of the RTCs gave information about missing data and 64% of the RTCs analyzed the PRO results in the context of other endpoints [15]. The sub-optimal protocols for reporting PROs in clinical trials are also confirmed by two recent articles focused, respectively, on ovarian cancer and advanced breast cancer, in particular regarding timing of administration of PROs instruments, monitoring of PROs compliance, handling of missing data, the analysis plan for PROs and results discussion [16,17].…”
Section: How To Include Pros In Clinical Trials: the Consort Pro Extementioning
confidence: 99%
“…Therefore, orphan drug manufacturers may lack the incentive to collect additional data, such as PROs, in the drug development process. Indeed, PROs are rarely reported in clinical trials of drugs for rare diseases [4,8]. Here, we sought to identify and characterise PRO claims in a comprehensive set of FDA orphan drug approvals from a 5-year period.…”
Section: Introductionmentioning
confidence: 99%